EMPREGO DE QUITOSANA EXTRAIDA DO CAMARÃO SETE-BARBAS Xiphopenaeus kroyeri (Heller, 1862) COMO SUPORTE PARA IMOBILIZAÇÃO DE ENZIMAS DIGESTIVAS - Azevedo, Rafael David Souto de; Brandão, Célio Henrique de Alcântara; Falcão, Kívia Vanessa Gomes; Ferreira, Amália Cristine Medeiros; Bezerra, Ranilson de Souza (Revista Nordestina de Zoologia, 2016)
Obtaining biomolecules, such as chitosan, from fish processing waste represent an excellent opportunity to recover bioactive molecules with unique properties and demonstrate how to make full use of natural resources. Thus, the present work aimed to obtain chitosan from shells and heads of the shrimp Xiphopenaeus kroyeri and uses it as support for immobilization of enzymes. Chitosan was successfully obtained after steps of decalcification, deproteinization, removal of pigments and deacetylation. Chitosan was magnetized and activated for immobilization using 12.5% glutaraldehyde. 1mg / mL solutions of Trypsin or Pepsin were incubated with activated chitosan. The best catalytic performance for both digestive enzymes was observed at 50 ° C and at pH 9.0. However, there are differences in the stability of the activity of these enzymes due to changes in pH and temperature. When observing the viability of chitosan to keep the enzyme stable after 5 weeks of storage, enzymes lost 20% and 60% of activity (trypsin and pepsin, respectively). After 10 replicate tests trypsin lost 17.6% and pepsin 42.04% of initial activity. With this, it is concluded that chitosan is a viable support for the immobilization of enzymes, especially for trypsin, and constitutes a sustainable alternative for marine activities currently carried out given the possibility of taking advantage of fish waste that is usually discarded.